Effects of Lightly Burnt MgO Expansive Agent on the Deformation and Microstructure of Reinforced Concrete Wall - Lanqing Yu; Min Deng; Liwu Mo; Jinxin Liu; Feifei Jiang (Advances in Materials Science and Engineering)
Compensation for shrinkages with three kinds of lightly burnt MgO expansive agent (LBMEA) is used in a reinforced concrete wall poured in the summer. Influences of the internal temperature history on the expansion of concrete and the microstructure of cement paste containing LBMEA were investigated. The results showed that LBMEA exhibited significant expansion around the end of the fall temperature stage; then, the expansion rate declined obviously, and concrete containing LBMEA with low hydration reactivity (140 s and 220 s) showed larger expansion than LBMEA with high hydration reactivity (60 s). Microstructural analysis indicated that brucite preferentially forms in the pores in cement paste containing LBMEA with high reactivity, but brucite mainly grows on the surface of the MgO particles in cement paste containing LBMEA with low reactivity during the early age. Paste containing LBMEA with low reactivity showed a larger volume of single brucite crystal than LBMEA with high reactivity, which further led to larger expansion in the latter than the former. The results revealed the expansion process of LBMEA and can help engineers select suitable LBMEA for application to actual engineering.